2017
DOI: 10.1155/2017/8267863
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA MIR4697HG Promotes Cell Growth and Metastasis in Human Ovarian Cancer

Abstract: Ovarian cancer is one of the three most common gynecological malignant tumors worldwide. The prognosis of patients suffering from this malignancy remains poor because of limited therapeutic strategies. Herein, we investigated the role of a long noncoding RNA named MIR4697 host gene (MIR4697HG) in the cell growth and metastasis of ovarian cancer. Results showed that the transcriptional level of MIR4697HG in cancerous tissues increased twofold compared with that in adjacent noncancerous tissues. MIR4697HG was di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…The Sp1-CD147 positive feedback loop may play a key role in the invasive ability of ovarian cancer cells. Down-regulation of the long non-coding RNA MIR4697 host gene (MIR4697HG) promotes the growth and metastasis of ovarian cancer cells by lowering levels of matrix metalloproteinase-9, p-ERK, and phosphorylated AKT (106). Downregulation of MIR4697HG inhibited cell migration and invasion (106).…”
Section: Erk/mapk Signalling In Tumour Invasion and Metastasismentioning
confidence: 99%
“…The Sp1-CD147 positive feedback loop may play a key role in the invasive ability of ovarian cancer cells. Down-regulation of the long non-coding RNA MIR4697 host gene (MIR4697HG) promotes the growth and metastasis of ovarian cancer cells by lowering levels of matrix metalloproteinase-9, p-ERK, and phosphorylated AKT (106). Downregulation of MIR4697HG inhibited cell migration and invasion (106).…”
Section: Erk/mapk Signalling In Tumour Invasion and Metastasismentioning
confidence: 99%
“…In our study, through transcriptomics-based screening, we found that the 13 identified lncRNAs exhibited close interactions with genes in the blue module. Studies have revealed that AATBC (Zhao et al, 2015), ADAMTSL4-AS1 (Annunziato et al, 2019), EPB41L4A-AS1 (Liao et al, 2019), MIA-RAB4B (Thean et al, 2017), MIR4697HG (Zhang et al, 2017a), GAS5 (Ni et al, 2019), SNHG12 (Tamang et al, 2019), MSX2P1 (Qiao et al, 2018), and LINC00852 (Liu et al, 2018b) are related to tumorigenesis and tumor progression in multiple cancers, such as bladder, breast, colorectal, and ovarian. Apart from the nine lncRNAs identified in biological experiments, LOC254896 (Singh et al, 2018), LINC01000 (Mitchell et al, 2017), LINC00893 (Li et al, 2019a), and LINC00537 (Li et al, 2017b) were also reported to be significantly differentially expressed between diseased and normal tissues in some transcriptional profiling analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to MALAT1, HOX transcript antisense intergenic RNA (HOTAIR) is closely related to the occurrence and development of tumor metastasis ( 20 23 ). Zhang et al ( 24 ) found that MIR4697 host gene (MIR4697HG) in cancerous tissues increased compared with that in adjacent noncancerous tissues. It could promote OC growth and metastasis.…”
Section: Discussionmentioning
confidence: 99%